Implementation of Distribution Non-Cash Food Aid (BPNT) in Reducing The Expenditure Burden of Poor Families Based on an Islamic Perspective: Case Study of Aek Hamlet West Torop, Asam Jawa Village, District. Torgamba, District. South Labuhan Batu - Dini Rahmayani; Maidalena; Aqwa Naser Daulay (Jurnal Manajemen Bisnis, 2024)
Non-Cash Food Assistance (BPNT) is a central government program to help the poor who are food insecure. The purpose of this study is the implementation of non-cash food assistance expenditures in reducing the expenditure burden of poor families. This research uses a qualitative approach that produces descriptive data, by interviewing two poor people and one government. The data collection techniques applied are interviews, observation and documentation. The results of this study indicate that poverty reduction so far has only changed from the food subsidy system (Raskin / Rastra) with an in-kind scheme to the BPNT food assistance system with a non-cash scheme. each poor family receives assistance of Rp. 200,000, -. The implementation of the assistance program in reducing the expenditure burden of poor families reaches an effectiveness level of 66.57%, this shows "good enough" and can reduce the expenditure burden of poor families by 55%. This is in accordance with Islamic values, namely Nafs (soul), Maal (property), Nasab (offspring) in sharia. The implementation of the BPNT program in various regions has been quite effective but the implementation has not met the 6 Target principle (right target, quantity, time, price, quality, and administration). The main obstacle related to the achievement of the program's target is that the data on Beneficiary Families (KPM) has not been updated properly. In terms of food groups, the food assistance received by poor families classified as KPM participants is quite diverse but with a decreasing quantity over time.